ПОМОШНИОТ ГЛАГОЛ сум ВО МАКЕДОНСКИОТ ЈАЗИК И ПОМОШНИОТ ГЛАГОЛ i- ВО ТУРСКИОТ ЈАЗИК - Leontić, Marija (Philological Studies, 2019)
Both Macedonian and Turkish have specific characteristics of grammar, but they also have simular items. Macedonian and Turkish have the verb to be (Macedonian сум, Turkish i-) with similar function in both languages. In Macedonian, there are: present tense, past tense, future tense and posibilitive of to be. In Turkish there are: present, past, reported and the conditional form of to be. This paper will examine the verb to be (Macedonian сум, Turkish i-) and their uses with nouns in Macedonian and Turkish, respectively.